PELATIHAN CALISTUNG (MEMBACA, MENULIS dan BERHITUNG) SEBAGAI UPAYA PEMBERANTASAN BUTA HURUF DAN PENINGKATAN MINAT BELAJAR PADA ANAK USIA DINI DAN SISWA/I SD DI DESA PELAWI SELATAN, KECAMATAN BABALAN, KABUPATEN LANGKAT - Edi Azwar; Mbera Mehuli; Antoni Antoni; Teddy Hardiansyah; Sri Hastuti Br Saragih (Universitas Islam Sumatear Utara, 2022)
Calistung is a skill that includes several abilities, namely the ability to read, write and count. The ability to read, write and count is a very important initial capital for a child in the learning process. With the ability to read, write and count can be a good start for a child so that the child can learn other knowledge, can communicate his ideas and can express himself. Therefore, failure in mastering this ability will result in fatal problems both to continue education to a higher level and in social life in society. Pelawi Selatan Village is one of UISU's partner villages in this village, there are still many children aged 4-9 years who cannot read and write and children aged 10-12 years who are not proficient in simple calculations, this is due to the lack of ability of parents to teach their children at home and the large number of educators who do not come from among educators. The methods used in this service activity are training and mentoring through tutoring and innovative and creative learning media such as learning while singing, abacuses and teaching media that are able to explore children's creativity. This service activity is one of the derivatives of the 2022 UISU KKNT work program which will be held on July 12 – August 19, 2022. This activity was carried out as many as 12 meetings from July 18 to August 10, 2022. Through this activity, it was obtained to increase the ability of children aged 3-8 years in reading, writing and also in addition and subtraction, as well as an increase in the ability of children aged 9-12 years in calculating multiplication and division. And also obtained the enthusiasm of children in learning which indicates an increase in the demand for learning in children.